THE EFFECT OF PROBLEM BASED LEARNING MODEL ON STUDENT’S ACHIEVEMENT AT LIGHT TOPIC IN 8TH GRADE JUNIOR HIGH SCHOOL - Avolen Berly Indah Siahaan; Derlina . (INPAFI (Inovasi Pembelajaran Fisika), 2015)
ABSTRACT The purpose of this study was to know the effect of Problem Based Learning Model on student’s achievement at Light topic in one of 8th grade Junior High School students. This study is a quasi experiment which involved two classes as sample. First the both of classes were given pretest then the experiment class was given PBL Model and control class was given Direct Instruction Model and after the both classes were given a different treatment they were given posttest and the result showed that the mean of experiment class was higher than control class. Based on result research there was an effect of PBL on student’s achievement.   Keywords: problem based learning, achievement